Performance analysis of hierarchical location management system for mobile-multi-agent system. (30th May 2019) - Singhal, Swati; Pathak, Heman
Location management of a Mobile Agent (MA) is necessary for a Mobile Agent System (MAS), in which many significant services are accomplished using MA communications that require specific location information. This paper gives the performance analysis of a Hierarchical Location Management System (HLMS) for mobile Multi Agent System (MUS) with the objectives to reduce the search and update cost. This work also discusses a mailbox-based approach to provide communication among MAs. Mailbox is a data structure which is used to store the messages for MAs. There are two different communication mechanisms (jump and full migration) with mailbox have been used. In jump migration MA's mailbox always resides at the local router and in full migration MA always carries its mailbox with it at the host it is executing. For jump migration MA periodically checks its mailbox to get the message. HLMS has been modelled using the timed Coloured Petri Net (CPN) tool. Performance of HLMS is then observed for identified parameters such as Trip Time (TT), Migration Rate (MR), Search Rate (SR), Network Overhead (ND) and Communication Time (COT). Simulation results show that HLMS can locate the MAs in a fault free environment but TT and ND decrease as intra-region MR increases.